PCR Primer Specific CaMV 35S Promoter to Detect Transgenic Soybean in Indonesia Commercial Soy Bean and Tempeh - Tri Joko Raharjo; Surajiman Surajiman (Universitas Gadjah Mada, 2017)
In the framework of the supervision and enforcement of the regulation regarding the content of soybean transgenic in food and processed foods such as tempeh, a reliable testing method is indispensable. Performance specific primer PCR amplification with promoter of CaMV 35S tested to detect the presence of GMOs. The parameters tested were specificity, precision and cut off detection using CRM transgenic soybean. The method is reliable to detect transgenic soybean specifically and has the annealing temperature at 59 °C during the 30 cycle standard PCR condition. The method did not show any false positive and false negative results meaning good precision. The cut off the methods is up to 2 copies total DNA of soybean or less than 104 copies of the CaMV 35S promoter. Observation to the commercial soybeans and tempeh found that most of the commercially available soybean in Indonesia are transgenic (8 of 10 sample) while all tested tempeh sample were detected have been fermented from transgenic soybeans.